The Efficacy of Acceptance and Commitment Therapy on Metacognitions and Anxiety in Women Outpatients with Generalized Anxiety Disorder in Iran - Fathi, Rayhan; Khodarahimi, Siamak; Rasti, Ali (Canadian Journal of Counselling and Psychotherapy, 2017)
The purpose of the present study was to examine the comparative effectiveness of acceptance and commitment therapy (ACT) in the treatment of metacognitions and anxiety among women with generalized anxiety disorder. In total, 40 self-referred female outpatients were examined within a randomized controlled trial. Patients were allocated to ACT and waitlist control groups. Metacognitions and anxiety symptoms were measured by the Metacognitions Questionnaire and the Beck Anxiety Inventory at baseline, posttreatment, and 2-month follow-up. Analyses showed that the therapeutic group had improved significantly whilst the control group had remained unchanged.